2008
DOI: 10.1529/biophysj.107.121079
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Geometry and Internucleosomal Interactions Control the Chromatin Fiber Conformation

Abstract: Based on model structures with atomic resolution, a coarse-grained model for the nucleosome geometry was implemented. The dependence of the chromatin fiber conformation on the spatial orientation of nucleosomes and the path and length of the linker DNA was systematically explored by Monte Carlo simulations. Two fiber types were analyzed in detail that represent nucleosome chains without and with linker histones, respectively: two-start helices with crossed-linker DNA (CL conformation) and interdigitated one-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
152
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(180 citation statements)
references
References 66 publications
28
152
0
Order By: Relevance
“…The somewhat smaller compaction values than ϳ10 nucleosmes/11 nm previously reported for chromatin fibers with similar DNA linker length by EM of Mg 2ϩ -compacted chromatin (17) and computational modeling (13,19) are likely because of sampling limitations and neglected internucleosomal interactions [e.g., hydrogen bonding between histone surfaces (40)]. Both our approaches, however, yield a similar (5S) increase in sedimentation constant with Mg 2ϩ ions.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The somewhat smaller compaction values than ϳ10 nucleosmes/11 nm previously reported for chromatin fibers with similar DNA linker length by EM of Mg 2ϩ -compacted chromatin (17) and computational modeling (13,19) are likely because of sampling limitations and neglected internucleosomal interactions [e.g., hydrogen bonding between histone surfaces (40)]. Both our approaches, however, yield a similar (5S) increase in sedimentation constant with Mg 2ϩ ions.…”
Section: Resultsmentioning
confidence: 57%
“…For example, the Rhodes group showed that fiber compaction is both repeat length and linkerhistone dependent (18). Analyses of known structures by the Rippe group (19,20) also suggested the large impact of nucleosome geometry on fiber compaction and the possible role of linker histones in converting between 2 fiber forms. Their systematic Monte Carlo simulations also support the notion that nucleosome interdigitation explains higher order chromatin structure and that the nucleosome repeat length affects the internal structure of the chromatin fiber.…”
mentioning
confidence: 99%
“…Unexpectedly, the data revealed a step-wise increase in fiber packing density and diameter. Modeling of these fibers predicted the existence of multi-start fibers with several nucleosome stacks Wong et al 2007;Depken and Schiessel 2009;Kepper et al 2008), but did not provide a uniform explanation for the observed step-wise changes in fiber parameters.…”
Section: -Nm Fibermentioning
confidence: 90%
“…However, the assumption of uniform interactions between adjacent nucleosomes, such as between the two H2A–H2B dimers seen in the crystal structure 5, results in the dyad axes pointing radially along the nucleosomal stack because each octamer must rotate in the same sense relative to its preceding neighbour. This constraint is typical of the many models that have been proposed for the structure of the compact chromatin fibre 5, 13, 14, 15, 17. Nevertheless, Schalch et al .…”
Section: Relation To Previous Workmentioning
confidence: 96%
“…Unexpectedly the data revealed a step‐wise increase in fibre‐packing density and diameter. Modelling of these fibres predicted the existence of multistart fibres with several nucleosome stacks 14, 15, 16, 17 (Table 1) but did not provide a uniform explanation for the observed step‐wise changes in fibre parameters.…”
Section: Tablementioning
confidence: 97%